Diversity Pattern of Habitats and Vascular Plant Species in Tapkeshwari Hill Ranges in the Kachchh Island, Gujarat, India - Joshi, Ekta B.; Jaln, B. K.; Joshi, P. N. (Indian Forester, 2011)
Tapkeshwliri Hill Ranges (THR) are located close to Bhuj city - district headquarter (7 kms) and provide high diversity of floral species in various vegetation types or habitats i. e. Euphorbia Scrub, Prosopis scrub, Thorn Mixed Scrub, Open Scrub, Thorn Mixed Forest, Acacia senegal Forest,Anilotica Forest and Salvadora Mixed. In the July- September (2006,2007 and 2008), the vegetation was sampled along fourteen altitudinal transects within five hillock clusters, from the top (270 m.a.s.l.) down to l50 m amsl, on ten main hillock ranges in the THR. With the increase of altitude the dominant plant cover changes from a thorn-mixed community, narrow leaves plants, to a woody shrub community and finally, stunted thorny plants with degraded open grasses. The maximum concentration of species number (Abundance) and diversity index (H’) observed in the middle slope indicates that the diversity index value and altitudinal range are inversely proportional. The high species diversity index or abundance in the altitudinal range of 201-225 m means greater effort should be made focused on conservation on plants diversity of this area.